Betulinic acid, isolated from the leaves of Syzygium cumini (L.) Skeels, ameliorates the proteinuria in experimental membranous nephropathy through regulating Nrf2/NF-κB pathways. (25th August 2017) - Sutariya, Brijesh; Taneja, Neetika; Saraf, Madhusudan
Abstract: Membranous nephropathy (MN) is associated with increased oxidative stress and inflammatory markers in the kidney. Betulinic acid (BA) is a potent antioxidant and anti-inflammatory compound isolated from the leaves of Syzygium cumini (L.) Skeels. In the present study, we investigated the effects of BA on experimental MN in rats and explored the mechanisms by which it enhances antioxidant activities and resolves inflammatory condition in experimental MN. Passive Heymann nephritis (PHN) was induced in Sprague-Dawley rats by a single tail vein injection of anti- Fx1A antiserum. The rats were orally administered BA (25 and 50 mg kg −1  d −1 ) or dexamethasone (DEX; 0.07 mg kg-1, reference compound) for 4 weeks after the induction of PHN. Blood, urine, and kidney tissue were collected for analysis at the end of the study. Treatment of PHN rats with BA or DEX significantly attenuated renal dysfunction, histopathological alterations and reduced immune complex deposition in the kidneys. Furthermore, BA ameliorated mRNA and protein expression of NF-κB, iNOS, TNF-α, Nrf2, HO-1 and NQO1 in the kidney. BA also restored malondialdehyde level and antioxidant enzyme activities in the kidney. In a nutshell, the protective effect of BA can be explained by its anti-inflammatory and anti-oxidant activities, which in turn is due to downregulation of NF-κB pathway and activation of Nrf2. The results indicated that BA can effectively suppress experimental PHN in rats by regulating Nrf2/NF-κB pathways. Graphical abstract: Highlights: Membranous nephropathy is a common cause of the nephrotic syndrome in adults. Betulinic acid is a potent anti-oxidant and anti-inflammatory compound isolated from the leaves of Syzygium cumini (L.) Skeels. Betulinic acid ameliorates the proteinuria in experimental membranous nephropathy through regulating Nrf2/NF-κB pathways.